Comprehensive investigation of radiofrequency/analog parameters in a ferroelectric tunnel field-effect transistor. (21st January 2022) - Saha, Rajesh; Goswami, Rupam; Bhowmick, Brinda; Baishya, Srimanta
Abstract: In this paper, the effect of ferroelectric (FE) layer thickness ( t FE ), coercive field ( E c ), remnant polarization ( P r ) and saturation polarization ( P s ) on the transfer characteristic is highlighted for a FE tunnel field-effect transistor (Fe-TFET) through a commercial technology computer-aided design simulator. Further, we have reported the radiofrequency (RF)/analog parameters such as transconductance, output conductance, gain, gate capacitance and cut-off frequency for a wide range of FE parameters in a Fe-TFET. An improved RF/analog performance and transfer characteristic are obtained for a low value of t FE and P r, whereas these behaviors are degraded at high values of P s and E c .